Inter-hospital cardiorespiratory telemonitoring of newborns and infants: a wellworking example of a hub and spoke network - Cinzia Arzilli; Monica Annunziata; Carola-Maria Ernst; Marta Peruzzi; Chiara Macucci; Saverio Pochesci; Niccolò Nassi (BMC, 2023)
Abstract Background Patients who experience cardiorespiratory events usually have to be moved to specialized centers to perform cardiorespiratory studies. To avoid the transfer of these patients to specialized centers, a network has been created based on an interchange system, where the recordings were uploaded in unspecialized centers (spokes) and downloaded by the Sleep Disorders Breathing (SDB) Center (hub) to be analyzed. Methods The inter-hospital network was established in November 2008. Initially only 3 non-tertiary hospitals in the Tuscany Region joined the network. Currently, 12 Tuscany hospitals are included. Results From November 2008 to December 2020, 625 recordings were collected belonging to 422 infants. No recurrent life-threatening episode or infant death occurred in the study population and none of the infants needed to be readmitted or be moved to a tertiary center, except infants who underwent home monitoring. The discharge diagnoses belong to the following categories: apnoea, respiratory problem of the newborn, syncope, gastroesophageal reflux, altered consciousness, transient loss of consciousness and cyanosis. Conclusions This study shows that the inter-hospital network is an efficient system that allows accurate and safe management of infants at risk for apnoea, bradycardia, and hypoxemia to remain in unspecialized centers, avoiding unnecessary transfers of patients and over - hospitalizations.